Makna Simbolik Dalam Budaya “Megengan” Sebagai Tradisi Menyambut Bulan Ramadhan Di Desa Blimbing Sari - Amalia Rohmatin Nazili; Mulia Putri Khasanah; Taswirul Afkar (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This article examines the symbolic meaning of the megengan tradition. The Megengan tradition is a ritual carried out before the month of Ramadan. This search was carried out in Blimbing Sari Village, Sooko District, Mojokerto Regency, East Java Province. The Megengan tradition in this hamlet has a unique implementation technique, namely Apem Cake, one of the obligatory dishes in the traditional tradition (Megengan People). As time goes by, many residents of Blimbing Sari Village continue to carry out these customs according to what was taught by the elders, while others apply a more practical approach. The meaning of the megengan traditional symbols for the people of Blimbing Sari Village can be studied by looking at existing events. Interviews, observations, and documents are some of the data sources used in qualitative research. Informant replies from interviews will be classified based on research objectives.